The impact of social media influencers on the consumer’s purchase intentions regarding beauty products : exploring the effects of source-credibility - Pereira, Carolina Fialho Inácio Mateus (2022)
In the past few years, many beauty companies have chosen to follow a recent marketing strategy, to promote their products/services, called influencer marketing. This new concept is the result of a fast growth of social media platforms and consequently the rise of social media influencers. This dissertation was developed to evaluate how social media is being used as a platform for influencers and understand how influencers affect purchase intentions, regarding the beauty industry. The dimensions of expertise, trustworthiness and attractiveness were considered mediators of credibility in purchase intentions. Therefore, a survey was conducted with 132 valid responses obtained. The results demonstrate that consumers prefer to search for information, regarding beauty products, through social media influencers rather than the brands themselves, and that they are more likely to purchase a beauty product when it has been advertised by a social media influencer rather than when it is advertised by the brand. Moreover, it was found that consumers’ purchase intentions are not higher for beauty products advertised by social media influencers who are perceived as experts, however, are higher for those who are perceived as trustworthy and attractive, and these mediate the effect of credibility on purchase intentions.